Caste, social networks and variety adoption - Gupta, Ishika; Veettil, Prakashan Chellattan; Speelman, Stijn (SAGE Publications, 2020)
Social networks influence technology diffusion but targeting formal leaders (institutional central nodes) may lead to distributional consequences. This paper analyzes the role of informal social networks in technology diffusion in a socially hierarchical caste-based society. Often, information flow and technology diffusion are constrained by social and economic boundaries where informal nodes such as caste play a very decisive role in everyday life. Proper targeting and dissemination of technology to the marginalized sections of society are very important for their development. We observed that only one-fourth of farmers cultivate newer varieties which include hybrids and recently released high yielding varieties. The results showed that individuals belonging to marginal groups are influential and act as informal leaders when they are the dominant caste in the village. Progressive farmers are found to fail in disseminating new varieties, and targeting influential informal leaders who belong to the dominant caste of the village appears to be a better strategy. Among non-dominant caste members, influential leaders belonging to Other Backward Classes (OBCs) or Scheduled Tribes (STs) are more desirable targets than other caste groups. The more concentrated a network is in terms of its caste composition, the faster will be the spread of any technology.